Dampak Kewirausahaan terhadap Pertumbuhan Ekonomi: Systematic Literature Review - Sarah Sakiran Salsabila; Wening Patmi Rahayu; Andy Prasetyowati (SENTRI: Jurnal Riset Ilmiah, 2026)
Entrepreneurship is one of the fundamental elements in stimulating economic development, especially through job creation, increasing innovation, and strengthening national competitiveness. However, research results on the effects of entrepreneurship on economic growth are still varied and scattered across various country contexts and methodological approaches. Therefore, the purpose of this study is to systematically review the literature examining the effects of entrepreneurship on economic growth using the Systematic Literature Review (TLS) method. The review process takes place through screening reputable academic articles published in indexed national and international journals in the last decade. This screening is carried out through several steps, including identification, selection, eligibility, and inclusion based on predetermined criteria. The research results show that entrepreneurship has a positive and significant impact on economic growth, particularly through increased productivity, technological innovation, and the development of small and medium enterprises (SMEs). Furthermore, supporting factors such as government policies, the quality of human resources, access to financing, and the entrepreneurial ecosystem also strengthen this relationship. However, a number of studies also indicate variations in the impact of entrepreneurship depending on the level of economic development and regional characteristics. The findings of this study are expected to provide theoretical contributions to the development of entrepreneurship studies and become considerations for the formulation of economic policies that focus on strengthening sustainable entrepreneurship.